975 Peripheral Tissue Nirs Oximetry: Reproducibility and Dynamic Range of Invos 5100C, Nonin Equanox, and Fore-Sight. (October 2012) - Hyttel-Sørensen, S; Hessel, T Witzner; Greisen, G
Abstract : Background and Aims: Near infrared spectroscopy (NIRS) could be a valuable tool in the NICU, but implementation into standard clinical care has yet to been seen. Different absolute values and dynamics of different devices and poor reproducibility could be the cause. Present study is a comparison between the adult sensors of INVOS 5100C, FORE-SIGHT and NONIN EQUANOX 7600. Methods: 10 repositionings on the same spot and 10 repostionings on slightly differing spots during steady state on the adult forearm followed by 6 cuff inflations to 250 mmHg and subsequent tissue deoxygenation. Reproducibility was estimated by the within-subject standard deviation, Sw, and dynamic range by the difference between the pre- and post-cuff inflation rStO2, ΔrStO2. Results: 10 adults participated. All with double skinfold less than 10 mm. Mean rStO2 was 71.1% (CI 68.4–73.9%), 68.1% (CI 65.2–71.0%), and 65.1% (95% CI 63.3–67.0%) with INVOS, NONIN, and FORE-SIGHT, respectively. INVOS gave significantly higher values than FORE-SIGHT (p=0.003). All other differences were insignificant. Reproducibility of FORE-SIGHT was best, while the reproducibility of NONIN was worst (table 1). Same-site reproducibility and various-site reproducibility was equal. In pairwise comparisons ΔrStO2 of NONIN, INVOS and FORE-SIGHT were significantly different (all p<0.0001)(table 2). The signal-to-noise ratio, i.e., ΔrStO2 /Sw, was 17.6, 14.5, and 12.5 for FORE-SIGHT, INVOS and NONIN, respectively. Conclusion: The different absolute values and dynamic ranges will make comparison of data collected with different devices difficult.